Globalization, the Palestinian economy, and the “peace process” - Samāra, ʿĀdil (Social justice, 2000)
Part of a special issue on neoliberalism, militarism, and armed conflict. The Palestinian economy, as the weak counterpart to that of the Israelis, needs more protectionism and economic detachment from the Israeli economy. Despite the initiation of a “peace process,” those parts of the occupied territories that have come under the jurisdiction of the Palestinian Authority (PA) have continued to be dominated by Israeli economic policies. Indeed, the PA's blind commitment to neoliberalism has led to sharper class differentiation, corruption, and polarization. Moreover, as long as the peace process—sponsored by the U.S., which is the chief controller of globalizing financial institutes—continues, the occupied territories will be affected in an economic and social sense to the extent that PA policies will be globally—not internally—geared.